Evaluation of killed Aeromonas hydrophila whole cell vaccine against acute infectious abdominal dropsy in Indian major carps - Shome, Rajeshwari; Shome, B R (Indian Journal of Fisheries, 2011)
A whole cell vaccine was prepared by using a formalin killed highly virulent strain of Aeromonas hydrophila isolated from Indian major carps suffering from acute infectious abdominal dropsy in Andaman. Ten numbers each of Cirrhinus mrigala, Catla catla and cat fishes were vaccinated by intraperitoneal (I/P) injection and immersion bath. Four weeks after vaccination, the efficacy was tested by challenging with virulent strain of A. hydrophila @ 1.5 x 109/0.2ml/fish by I/P. The relative percentage of survivability (RPS) was observed at 100, 75 and 60 in 1/ P vaccinated group against 45, 25 and 20 in immersion group respectively. Strong agglutinating and precipitating antibodies were present in I/P vaccinated group in contrast to mild delayed type reaction in immersion bath vaccinated group. However, wide range of individual variation in both the agglutinating and precipitating antibodies was observed. Microscopic observation of blood cells from vaccinated and control groups and the primary antigen-antibody reactions indicated that both cellular and humoral antibodies are involved in protection, and even the detectable level of agglutinating as well as precipitating antibodies are enough for protection. Since I/P vaccination in fish population is not a feasible proposition, a live attenuated vaccine for use either as immersion or in the form of biofilms is urgently required